A Tamil Muslim Sūfï - More, J. B. P. (Islam and Christian-Muslim relations, 1999)
The Sufi biography has a certain historical value and significance, when we take into account the historical context and the social environment in which the Sufi comes into existence and evolves. In this paper, I have made a modest attempt in this direction, first by portraying the life history of the obscure, little known Tamil Sufi of Pondicherry, saint Sayyid Ahmad Moula Sahib, reconstituted exclusively from oral sources and then by unravelling its historical and social value. Though the life history of the Sufi is always shrouded in mystery, yet all is not mystery, when we consider it in the light of the actual social and historical background, if available. This is not always an easy task.